Numerical Simulation Research and Application of Support Design of Broken Rock Mass in Submarine Gold Mine - Yu-yun Fan; Ming-wei Jiang; Li Cheng; Xi Wang; Xing-quan Liu; Chunlong Wang; Kexu Chen (Advances in Civil Engineering)
In order to solve the problem that the broken rock mass is easy to collapse and fall during the excavation of a submarine gold mine, two kinds of bolt-mesh-concreting combined support schemes are designed by means of field engineering geological investigation, indoor rock mechanics test, rock mass quality classification, and theoretical analysis. We use the numerical simulation for verification and carry out the field industrial test. The results show that the stability grade of broken surrounding rock is III–IV; both schemes can effectively control the deformation and failure of surrounding rock. Compared with the unsupported scheme, the maximum roof displacement in the scheme using roadway roof and sidewall support is reduced by 26.9%, the maximum thickness of the roof plastic zone is reduced by 58.2%, and the volume of the surrounding rock plastic zone is reduced by 26.32%. The bolt-mesh-shotcrete support has good control effect on the loose deformation of surrounding rock, which can effectively prevent the roof collapse and sidewall spalling of roadway. The field industrial test of support scheme meets the stability control requirements of broken rock mass in mines, and the application effect is obvious. The research results presented in this study provide valuable technical guidance and essential insights for the design of support systems in other similar mining projects, contributing to the effective control and stability of broken rock masses during excavation.